A synopsis of Macropharynx (Apocynaceae) in Colombia, with comments on floral characters, and a new combination - Morales, J. Francisco; Endress, Mary E. (Phytotaxa, 2024)
A synopsis of Macropharynx (Apocynaceae) in Colombia is provided. Five species are reported, a key is provided, and a new combination is made. Free corona lobes are reported in Macropharynx renteriae A.H. Gentry for the first time in the genus. A lectotype is selected for Peltastes isthmicus Woodson, a second-step lectotypification is completed for Echites spectabilis Stadelm. and a neotype is designated for Temnadenia stenantha Woodson. Pictures of all the species are included. Macropharynx renteriae is reported for the first time to Panama.